2014
DOI: 10.1039/c3an01718d
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of carbon–platinum hybrid nanostructure architecture for amperometric biosensing

Abstract: Carbon and noble metal nanomaterials exhibit unique properties that have been explored over the last few decades for developing electrochemical sensors and biosensors. Hybridization of nanometals to carbon nanomaterials such as graphene or carbon nanotubes produces a synergistic effect on the electrocatalytic activity when compared to either material alone. However, to date there are no comparative studies that directly investigate the effects of nanocarbon concentration and nanocomposite arrangement on electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 32 publications
4
51
0
Order By: Relevance
“…Previous work by Vanegas et al (2014) demonstrated the capability of this hybrid nanomaterial to enhance the electrochemical performance of amperometric sensors by vastly increasing the contact interface, as well as potentiating the electrical behaviour of the transducing component. The relatively high electroactive area of the rGO/nPt platform also permits larger enzymatic loading onto the sensor surface (compared to other nanomaterial platforms such as carbon nanotubes; see Vanegas et al (2014) for detailed discussion). Distribution of the enzymes within the hydrogel/sol-gel matrix was characterized by LSCM to emphasize the presence and distribution of each type of enzyme (right panel of Fig.…”
Section: Biosensor Fabrication and Performance Characterizationmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous work by Vanegas et al (2014) demonstrated the capability of this hybrid nanomaterial to enhance the electrochemical performance of amperometric sensors by vastly increasing the contact interface, as well as potentiating the electrical behaviour of the transducing component. The relatively high electroactive area of the rGO/nPt platform also permits larger enzymatic loading onto the sensor surface (compared to other nanomaterial platforms such as carbon nanotubes; see Vanegas et al (2014) for detailed discussion). Distribution of the enzymes within the hydrogel/sol-gel matrix was characterized by LSCM to emphasize the presence and distribution of each type of enzyme (right panel of Fig.…”
Section: Biosensor Fabrication and Performance Characterizationmentioning
confidence: 98%
“…Based on a methodology similar to the one described by Vanegas et al (2014), a nanocomposite of reduced graphene oxide and nanoplatinum (rGO/nPt) was deposited on the tip of a Pt/Ir microelectrode (PI20033.0A10 MicroProbes©, 1-2 mm tip diameter, Gaithersburg, MD). Briefly, a GO solution was prepared in DI water at a concentration of 2 mg/mL, followed by ultrasonication for 30 min.…”
Section: Nanomaterials Platform and Protein Immobilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the methodology described in previous work by our group 12,13 , amorphous platinum nanoclusters (nPt) were formed on the surface of the electrode via simultaneous sonication/electroplating at 10 V for 30 seconds in a solution of 1.44% chloroplatinic acid and 0.002% lead acetate. A CeO/rGO suspension was prepared by mixing CeO, GO, and AA in a 1 ml:2 mg:8 mg ratio, followed by ultrasonication for 30 minutes.…”
Section: Nanomaterials Platform Depositionmentioning
confidence: 99%